COMPARATION OF RUBBER MILLING PROCESS TO PRODUCE NATURAL RUBBER COUMPOUNDS USING MODIFIED AND UNMODIFIED LOCAL CLAY FILLER - Abu Hasan; Martha Aznury; Indah Purnamasari; Muhammad Zaman; Robert Junaidi; Rahmaniar (BRIN Publishing (Penerbit BRIN), 2020)
COMPARISON OF RUBBER MILLING PROCESS TO PRODUCE NATURAL RUBBER COMPOUNDS USING MODIFIED AND UNMODIFIED LOCAL CLAY FILLER. Many researchers have studied the effect of modified clay as filler on rubber compounds for both natural rubber and synthetic rubber. Various chemicals are used as clay modifiers. In the rubber milling process, modified clay is directly used as filler after pretreatment with clay modifier. However, clay modifiers can also be milled together with original clay during the rubber mastication and milling process. Thus both of these methods certainly produce different physical properties, so the comparison of the two rubber milling processes is the focus of this research. The analysis of the curing characteristics and physical properties of vulcanized natural rubber was carried out with a rheometer and physical properties test units. Thermal analysis was carried out using TG/DTA and dispersion of filler on the rubber compound was analyzed by SEM. The results of the curing characteristic of the rubber compound and the physical properties of vulcanization showed that there was an effect due to the comparison of the rubber milling process. Modified clay using JH-S69 is better than JH-S69 milled with original clay and vice versa occurs in PEG 4000 which is used as clay modifier. PEG 4000 which is milled together with original clay produces curing characteristic and physical properties of vulcanization better than pretreatment of clay to be modified clay. This analysis is in line with the analysis using SEM.